A Review on the Relationship Between p53 Gene and Viruses in Endometriosis: Tinjauan tentang Hubungan Antara Gen p53 dan Virus pada Endometriosis - Khzal, Alaa Mahdy Obaid (Universitas Muhammadiyah Sidoarjo, 2025)
Ten percent of pre-menopausal women suffer from endometriosis which manifests as a chronic inflammatory disorder due to complicated and poorly understood pathogenesis. The relationship between P53 tumor suppressor genes and viral infections as causes of endometriosis needs complete evaluation in research. Studies conducted at the molecular level reveal endometriotic lesions display major P53 expression variations while functional regulation and defensive abilities change from somatic mutations and DNA polymorphisms in addition to epigenetic influences that block tumor-suppression operations. Multiple investigations have established that endometriotic tissues carry human papillomavirus (HPV) Epstein-Barr virus (EBV) and cytomegalovirus (HCMV) viral DNA sequences with varying frequency percentages. The proposed mechanisms study how viral oncoproteins activate P53 pathways in endometriosis development by damaging cell death systems and through their influence on inflammatory processes and genomic instability creation and cell motility changes. The review examines how such biological interactions impact endometriosis diagnosis and treatment options. Currently missing components of known analysis become apparent in this research as it points out needed study techniques for understanding the sophisticated relationship between sun-induced skin damage and Human Papillomavirus infections. Highlights: Endometriosis involves disrupted P53 function due to mutations, polymorphisms, and epigenetics. Viral DNA from HPV, EBV, and HCMV is found in endometriotic tissues, implicating infections in disease progression. Viral oncoproteins may alter P53 pathways, affecting inflammation, cell death, and genomic stability. Keywords: Endometriosis, P53 Tumor Suppressor, Human Papillomavirus, Viral Oncoproteins, Inflammation